Discussing the Elements that Caused Family Violence, Consequences, and Current Situation in Vietnam - Huong , Nguyen Thu; Tram, Vo Thi Bao (International Journal of Membrane Science and Technology, 2023)
: Family violence has long been a significant problem in society. It has had severe consequences in many societies. This article is a study of the problem of domestic violence in Vietnam. When evaluated objectively, the currently applicable legal regulations in solving it have not come to life. The interest and understanding of this field have not been studied in detail, and domestic violence has increased alarmingly. From the article’s perspective, the author will analyze domestic violence in Vietnam while pointing out its adverse effects. From here, directions and solutions for the future will be proposed. This article is based on library-based gathering and synthesizing of existing data. The study used journal articles, reports, news articles, and the constitution of Vietnam. The article established that domestic violence is a reality in Vietnam. Domestic violence is manifested in mental, physical, economic, and sexual ways. It was also established that women, children, and the elderly are the most affected. There is a need to broaden the scope of the "Law on Domestic Violence Prevention and Control"; authorities should ensure that the provisions of the 'Law on Domestic Violence Prevention and Control" are enforced consistently and comprehensively; the relevant authorities have to do more in the dissemination of information on how to control domestic violence; and there is a need to create a fund to help the victims of domestic violence in their recovery.